PENGUATAN PROFIL PELAJAR PANCASILA MELALUI PEMBIASAAN TAHFIDZ AL-QUR’AN DI SMPIT INSAN HARAPAN - Wahyunita, Annisa; Bariah, Oyoh; Makbul, M. (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Education can be interpreted simply as a human effort to increase physical and spiritual potential, with the aim of advancing positive values for themselves and society. As explained by the Indonesian Ministry of Education and Culture, there are three big problems related to the character of the current young generation or what is usually called Gen Z, including those who are still students, namely the lack of mutual respect (intolerance), harassment and bullying (bullying). Therefore, there is a strengthening of the profile of Pancasila students who pay attention to interdisciplinary learning and think about solutions to environmental problems. With the aim of forming Indonesian students into students with general competence in accordance with Pancasila values. Keywords: Independent Curriculum; Project for Strengthening Pancasila Student Profiles: Character Education.